DIVERSITY AND ABUNDANCE OF MARINE GASTROPODS ALONG CHENNAI AND CHENGALPATTU COAST OF TAMILNADU, INDIA - SUNDARI, S. ANGELINE SARAH; LIVINGSTONE, ANANTHI RACHEL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
A survey on the diversity and abundance of marine gastropods was undertaken along the coast of Chennai, and Chengalpattu Districts of Tamilnadu, India. The study was conducted in Ennore, Neelankarai, and Kovalam. A total of 41 species of gastropods belonging to 5 orders, 24 families, and 31 genera were identified. In all three sites, the species Murex tribulus was found to be in abundance, followed by Turritella duplicata, Turritella attenuata, and Babylonia spirata. Three genera of Bufonaria and Turritella were recorded. A total of 6 species were reported belonging to the family Muricidae. The maximum diversity of species was found to be in Ennore. It may be due to the estuarine habitat, more organic sediments, and other resources.